A Comparative Analysis of "Public Interest Claims" in US and Indian Legal Systems - Hadi Salehi; hossein sharifi (پژوهشهای حقوقی)
Public interest litigation (PIL) emerged as a distinct form of litigation originating from the historical trajectory and legal context of the United States. Initially shaped by America's legal associations and rooted in the civil rights movements of the mid-20th century, these litigations addressed the shortcomings in traditional democratic models. They serve as a mechanism to uphold the assurances enshrined in the legal framework, such as the Sani Law, catering to classes and individuals deprived of fundamental rights and human dignity. PILs are instrumental in granting marginalized segments of society access to judicial justice, primarily focusing on the safeguarding of their fundamental rights and the rectification of legal ambiguities. Moreover, they aspire to instigate 'social change,' where the outcomes extend beyond individual cases and can be applied to similar situations, amplifying their impact. Advocating for human rights principles stands as the underlying motive and impetus behind such petitions. Various nations, including India, have adapted and refined this litigation model to suit their distinct social contexts and legal structures. Notably, in India's legal system, the Supreme Court judges have spearheaded innovation, particularly in relaxing the stringent requirements for the plaintiff's general authority.